2020
DOI: 10.47836/pjtas.43.4.14
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Diets Containing Asyastasia gangetica and Brachiaria decumbens on Intake, Digestibility and Growth Performance of Growing Rabbits

Abstract: The beneficial effects of feeding rabbits with forages have been recommended. However, limited study has been made on feeding values of locally available forages in rabbits. Therefore, an experiment was conducted to evaluate the effect of Asyastasia gangetica and Brachiaria decunbens on intake, digestibility, and growth performance of rabbits. Twelve rabbits were distributed into three diets: (i) 100% commercial pellet as control (T1), (ii) 50% pellet plus Asyastasia gangetica ad libitum (T2), and (iii) 50% pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
2
0
1
Order By: Relevance
“…The DM and OM digestibility were higher (p < 0.05) in rabbits fed with diets T1 and T2 compared to those fed diets T3 and T4. The DM digestibility observed in this study ranged from 80.2% to 89.2%, and these values are similar to the reports of Ikyume et al (2019) but higher than the findings of Rahman et al (2020b). Likewise, the OM digestibility values in this study ranged from 48.4% to 74.0%, aligning with previous findings (Rahman et al, 2020b).…”
Section: Nutrient Digestibility and Growthsupporting
confidence: 91%
See 2 more Smart Citations
“…The DM and OM digestibility were higher (p < 0.05) in rabbits fed with diets T1 and T2 compared to those fed diets T3 and T4. The DM digestibility observed in this study ranged from 80.2% to 89.2%, and these values are similar to the reports of Ikyume et al (2019) but higher than the findings of Rahman et al (2020b). Likewise, the OM digestibility values in this study ranged from 48.4% to 74.0%, aligning with previous findings (Rahman et al, 2020b).…”
Section: Nutrient Digestibility and Growthsupporting
confidence: 91%
“…Notably, the EE contents of both ingredients used in this study were higher than the EE requirements (2.5-4.0%) for adult rabbits, as reported by the National Research Council (NRC) (1977). In contrast, the organic matter (OM) content of A. gangetica is similar to the findings by Rahman et al (2020b). The CP content is lower compared to the reports by Khalil (2016), who found that the CP content in A. gangetica was 23.2%.…”
Section: Nutritive Valuesupporting
confidence: 82%
See 1 more Smart Citation